Handling Complaints: Considerations for Prioritizing Complaints - Laliberté, Maude; Casgrain, Lynne; Volesky, Karena (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
Overstretched resources and steady increases in the number of complaints filed with the offices of the Quebec Service Quality and Complaints Commissioner prompted us to investigate the complaint-handling systems of health-related organizations operating in Commonwealth and Western European countries. We also examined guidelines used to identify higher priority files (i.e., urgent files). Urgent files can then be prioritized in terms of the time taken to provide a conclusion as well as the depth of the examination. A system where a small fraction of complaints is deemed “urgent” was preferred over systems where complaints are categorized into three or more priority levels, because files categorized in the lowest of three or more priority levels risk being neglected. Applying lessons from other systems and considering the Service Quality and Complaints Commissioner’s mandate, we identified three guiding criteria for determining whether files warrant urgent status: threat to safety, involvement of vulnerable person(s) and risk of recurrence (but only when coupled with safety issues). Since determining which files should be considered urgent is not straight forward, these broad criteria can be adapted and applied on a case-by-case basis.